2011
DOI: 10.1093/eurpub/ckr069
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and perceived environment in German adults

Abstract: Our findings suggest that the perceived environment is important to promote both MVPA and walking in rural and urban areas. To better understand environmental correlates in rural structures, we particularly need more specific studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 34 publications
2
28
1
1
Order By: Relevance
“…Studies in Hong Kong and mainland China demonstrated that the neighborhood surroundings/aesthetics were not associated with walking for recreation or transportation among general residents [17], [31]. However, the results from our study and that performed Hong Kong are inconsistent with the findings of reports from Western countries [32], [33]. This suggests that a high population density and urban design might influence the association between aesthetics and walking.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in Hong Kong and mainland China demonstrated that the neighborhood surroundings/aesthetics were not associated with walking for recreation or transportation among general residents [17], [31]. However, the results from our study and that performed Hong Kong are inconsistent with the findings of reports from Western countries [32], [33]. This suggests that a high population density and urban design might influence the association between aesthetics and walking.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the results, eight studies found an association 12,13,16,18,19,21,22,26 between perception of safety and PA practice, all indicating a direct association. Nonetheless, five studies did not show an association between these variables 17,20,[23][24][25] . Perception of safety varied among the following: overall perception of safety 12,13,19,[20][21][22]25 , safety against crimes 23,24 , fear of staying at home or leaving home during the day or night 16,17 , traffic safety 18 and safety against crimes and in traffic 26 .…”
Section: Resultsmentioning
confidence: 92%
“…Of all 13 articles selected, six were performed in Europe (four in Holland [16][17][18][19] , one in Germany 20 and one in the whole Europe 21 ), six in the Americas (three in the United States [21][22][23] and three in Brazil 13,24,25 ) an one in Africa (Nigeria 26 ). In the studies performed by Europeans and Americans, the majority of the sample was comprised of females and the most prevalent age group was adults and elderly individuals aged more than 60 years.…”
Section: Resultsmentioning
confidence: 99%
“…Walman e colaboradores (2012) 17 apresentaram resultados de associação individualmente por cada pergunta do questionário. Assim verificou-se que para indivíduos moradores de áreas rurais, "dificuldades percebidas no trá-fego" são empecilhos para prática de caminhada.…”
Section: Resultsunclassified